Food supply chain management - Bourlakis, Michael A.; Weightman, Paul W. H. (Blackwell Pub., 2004)
"Food Supply Chain Management" brings together the most important of these disciplines and aims to provide an understanding of the chain, to support those who manage parts of the chain and to enhance the development of research activities in the discipline. "Food Supply Chain Management" follows a 'farm to fork' structure. Each chapter starts with aims and an introduction and concludes with study questions that students in particular will find useful. Topics covered include the food consumer, perceived risk and product safety, procurement, livestock systems and crop production, food manufacture, retailing, wholesaling and catering. Special consideration is also given to supermarket supply networks, third party logistics, temperature controlled supply chains, organic foods and the U.S. food supply chain. A final chapter looks at the future for food supply chain management. -- Publisher description
Keywords: Farm produce -- Great Britain -- Marketing.; Food industry and trade -- Great Britain.; Marketing channels -- Great Britain.; elektronické knihy; electronic books